Ethnocultural Linguistic Component in Nechuy-Levytsky’s Idiostyle (Linguostylistic Studies, 2015)
This article is dedicated to the idiostyle of Ukrainian grate writer, classical author of the end of XIX-beginning of XX century – Ivan Nechuy-Levytsky. It is determined that relevant at that time national identity issues, preservation of distinctive culture and language, which are reflected in author’s prose, caused the using of corresponding vocabulary and syntax. Usage I. Nechuy-Levytsky represents a certain section of the synchronous Ukrainian literary language with his popular spoken, book, folk sources, with the fixation of new linguistic phenomena, caused by the international and intercultural contacts, as well as the search for individual artistic language thinking. Test literary texts – is a valuable material for studying the history of Ukrainian literary language of the second half of XIX century with the relevant factors interlingual interference. Key words: idiostyle, individual style, the history of Ukrainian literary language, ethnocultural sense, language issue, narrative text. References